ANALYSIS OF THE ROLE OF DPK, CAR, NPL IN DISTRIBUTING BANK LOANS TO UMKM - Br. Sebayang, Jesy Ulina; Napitupulu, Marsya; Syah Putri, Tantri Octora Dwi; Miraza, Zuwina (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This research paper analyzes the role of Third Party Funds (TPF), Capital Adequacy Ratio (CAR), and Non-Performing Loans (NPL) in the distribution of bank loans to Micro, Small, and Medium Enterprises (UMKM) in Indonesia. This study uses a quantitative approach, utilizing secondary data sources to assess the impact of these financial indicators on bank lending practices. It highlights the importance of UMKM as a critical component of the Indonesian economy, accounting for a large percentage of business forms in the ASEAN region, ranging from 88.8% to 99.9%. The findings show that Third Party Funds, measured using the natural logarithm to normalize the data distribution, play a significant role in facilitating bank lending. Furthermore, the study highlights the negative and significant influence of NPL on credit distribution, where a higher NPL ratio indicates increased credit risk for banks. Furthermore, the study discusses the importance of CAR as a measure of a bank’s financial health, showing that higher CAR is correlated with better lending capacity. Overall, this paper emphasizes the interconnectedness of these financial metrics and their collective impact on improving the accessibility of bank loans for UMKM, which is critical for economic growth and poverty alleviation in Indonesia.